Block interval training in highly-trained cross-country skiers - McGawley, K.; Juudas, E.; Holmberg, H. C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Short periods of intensified training elicit symptoms of overreaching within only 7 days (Halson et al. 2002). Despite this, block periodization of high-intensity interval training (HIT) has led to superior aerobic responses compared with traditional endurance training among trained alpine skiers and cyclists (Breil et al. 2010; Rønnestad et al. 2012).